A design consideration of heated bed's rapid levelling tool based on von misses stress using FEA simulation - Arief, Rudi Kurniawan; Adesta, Erry Yulian Triblas; Hannaf, Riyadh Ali Abdullah; Hilmy, Irfan (Institute of Electrical and Electronics Engineers Inc., 2020)
Currently, heated bed levelling method used in low cost FDM 3D printer is using spring and screw adjustment system that requires more effort and time. This is a part of ongoing research to design a novel leveling system for FDM 3D by introducing a new system to replace the screw system. Previous research has introduced a new concept design to quick and easy levelling of FDM 3D printer’s heated bed using staggered pin design. This paper is to analyze the staggered pin system by simulating various dimensions and materials using Finite Element Analysis (FEA) simulation software. Best configuration was analyzed by comparing the VMS value obtained from the simulation. Using FEA, 18 design configurations have been simulated and analyzed. All configurations are strong and safe to apply and can be carried on for further research but Polyethylene (PE) material obtained lowest VMS value and suggested to be chosen. PE material also good for mass production because it can be manufactured by using plastic injection molding and can be sold in relatively lower price.